2017
DOI: 10.1007/s00040-017-0563-x
|View full text |Cite
|
Sign up to set email alerts
|

Nest building by a neotropical social wasp using Cecropia trichomes as main construction material (Hymenoptera, Vespidae, Polistinae)

Abstract: Nest architecture is such a splendid product of social wasp behavior, there being a large diversity of nest types in the Neotropical fauna. Charterginus is a small wasp genus with six species recorded from Honduras through South America, and one species C. fulvus is notable for normally making nests with a very peculiar star shape. Few behavioral traits of this genus have been described, an exception being a record of cleptobiosis between Charterginus species and Azteca ants on Cecropia trees in Amazonia and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…They were never observed swallowing MBd aggregates. Observations on material brought by foragers to a C. fulvus nest on the MPEG campus (see Borges et al, 2017), indicated that MBd masses were shared with workers in the nest, in the same way as other collected materials.…”
Section: Charterginus Fulvus Behaviormentioning
confidence: 85%
See 2 more Smart Citations
“…They were never observed swallowing MBd aggregates. Observations on material brought by foragers to a C. fulvus nest on the MPEG campus (see Borges et al, 2017), indicated that MBd masses were shared with workers in the nest, in the same way as other collected materials.…”
Section: Charterginus Fulvus Behaviormentioning
confidence: 85%
“…In that respect, it is important to note that during parallel observations of a colony of C. fulvus at the Goeldi Museum campus, a large proportion of the observed foragers returned to the nest carrying trichomes and MBds. Further investigation showed that the observed nest was entirely constructed with trichomes collected on trichilia of Cecropia trees (Borges et al, 2017). Quantitative measurement of the relative importance of MBds as forage items should be undertaken in future studies of the foraging activities of those wasps.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation